THE APPLICATION OF COOPERATIVE LEARNING MODEL OF THETYPE OF INVESTIGATION TEAM TO IMPROVE THE ABILITY OF PROBLEM SOLVING IN MATHEMATICS LEARNING MATERIAL FRACTIONS IN THE STORY - Lestari, Eria Puspa; Lesmana, Windri Sari; Agra, Hana Sakura Putu (COLLASE (Creative of Learning Students Elementary Education), 2018)
Mathematical problem solving ability is one of the capabilities of the perceived difficult by students.Researchers working to improve students ' ability in solving math problems and also enhance the learning interest of students.One effort that can be done is with the selection of an effective learning model and operates on problem solving learning model cooperative type i.e. the investigation team.Class action research aims to find out students ' problem-solving ability improvement and learning interest of students.Research methods the research done is a class act. Implementation of the action classes each cycle addresses the matter to calculate the fractions in the form of a question of the story until it reaches the ketuntasan student learning outcomes.Research done in class IV (four) SDN 227 Margahayu North of Bandung city year lessons 2017-2018 with the number of learners 29 people.The achievement of the learning outcomes of students with 70 KKM is at pre-cycle average values gained 64.21 with pesentase ketuntasan 41.37%, cycle I gained an average rating of 76.21 with pesentase ketuntasan 68.96%, whereas in the achievement of the learning outcomes II cycle students gained an average rating of 86.03 with pesentase ketuntasan 89.65%.